2021
DOI: 10.1177/03000605211049943
|View full text |Cite
|
Sign up to set email alerts
|

Comparative efficacy of azithromycin versus clarithromycin in combination with beta-lactams to treat community-acquired pneumonia in hospitalized patients: a systematic review

Abstract: Objective The objective was to compare the efficacy of azithromycin and clarithromycin in combination with beta-lactams to treat community-acquired pneumonia among hospitalized adults. Methods Five databases (PubMed, Google Scholar, Trip, Medline, and Clinical Key) were searched to identify randomized clinical trials with patients exposed to azithromycin or clarithromycin in combination with a beta-lactam. All articles were critically reviewed for inclusion in accordance with the Preferred Reporting Items for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 43 publications
0
6
0
Order By: Relevance
“…39 It has been found that patients who receive a macrolide-β-lactam combination have shorter hospital stays. 40 The pharmacokinetic profiles of azithromycin are less complex, which may influence the therapeutic decision when combining a macrolide with a β-lactam antibiotic and other drugs. [41][42][43][44][45] Furthermore, the longer half-life of azithromycin allowed for a single-dose daily regimen aids in improving adherence and higher rates of clinical cure at the end of treatment.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…39 It has been found that patients who receive a macrolide-β-lactam combination have shorter hospital stays. 40 The pharmacokinetic profiles of azithromycin are less complex, which may influence the therapeutic decision when combining a macrolide with a β-lactam antibiotic and other drugs. [41][42][43][44][45] Furthermore, the longer half-life of azithromycin allowed for a single-dose daily regimen aids in improving adherence and higher rates of clinical cure at the end of treatment.…”
Section: Discussionmentioning
confidence: 99%
“…[41][42][43][44][45] Furthermore, the longer half-life of azithromycin allowed for a single-dose daily regimen aids in improving adherence and higher rates of clinical cure at the end of treatment. 40 The study found reservations regarding fluoroquinolones (FQs) and doxycycline. A Clinical perspective would suggest that this was a reasonable strategy.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In a prospective cohort study of patients with severe CAP, the combination of beta-lactam and azithromycin was also associated with a significantly lower 30-day mortality (OR = 0.12, 95% confidence interval (CI): 0.007–0.57) compared with beta-lactam alone [ 26 ]. A meta-analysis of beta-lactam and macrolide combination therapy for CAP discovered that azithromycin-based combinations had higher clinical success rates than clarithromycin-based combinations (87.55% vs. 75.42%) [ 27 ]. A multicenter, multinational observational study of patients with severe CAP suggested that the combination of aspirin with CAM or azithromycin was associated with the 30-day survival rate (HR, 0.71, 95% CI: 0.58–0.88, p = 0.002) [ 28 ].…”
Section: Discussionmentioning
confidence: 99%
“…While one systematic review and meta-analysis found no comparator studies between erythromycin and azithromycin, studies comparing erythromycin with clarithromycin showed erythromycin to be less effective [ 104 ]. Furthermore, a systematic review of azithromycin versus clarithromycin in combination with a BL, showed a higher success rate for azithromycin-based combinations, but a shorter hospital length of stay with clarithromycin-based combinations [ 105 ].…”
Section: Are the Benefits Of Combination Antibiotic Therapy Specifica...mentioning
confidence: 99%